Congenital Chagas Disease in the United States: The Effect of Commercially Priced Benznidazole on Costs and Benefits of Maternal Screening - Perez-Zetune, Victoria (Am J Trop Med Hyg, 2020)
Chagas disease, caused by Trypanosoma cruzi, is transmitted by insect vectors, and through transfusions, transplants, insect feces in food, and mother to child during gestation. An estimated 30% of infected persons will develop lifelong, potentially fatal cardiac or digestive complications. Treatment of infants with benznidazole is highly efficacious in eliminating infection. This work evaluates the costs of maternal screening and infant testing and treatment for Chagas disease in the United States, including the cost of commercially available benznidazole. We compare costs of testing and treatment for mothers and infants with the lifetime societal costs without testing and consequent morbidity and mortality due to lack of treatment or late treatment. We constructed a decision-analytic model, using one tree that shows the combined costs for every possible mother–child pairing. Savings per birth in a targeted screening program are $1,314, and with universal screening, $105 per birth. At current screening costs, universal screening results in $420 million in lifetime savings per birth-year cohort. We found that a congenital Chagas screening program in the United States is cost saving for all rates of congenital transmission greater than 0.001% and all levels of maternal prevalence greater than 0.06% compared with no screening program.